Pengaruh Perubahan Lingkungan Terhadap Kinerja Karyawan Pada Bank Syariah Indonesia - Hasibuan, Nurliati; Yurmaini, Yurmaini; Erliyanti, Erliyanti (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of environmental changes on employee performance at the Indonesian Sharia Bank in Medan City and to determine the magnitude of the influence of Environmental Changes on Employee Performance at the Indonesian Sharia Bank in Medan City. The population in this study were 115 respondents with the sampling technique using purposive random sampling. The results of the study show that: 1) Based on the t-test above, it shows that the significance value for the Environmental Change variable (X) is 0.019 <0.05, so it can be concluded that H1 is accepted and H0 is rejected 2) Based on the F test above it shows the value the significance for the effect of X on Y simultaneously is 0.019 and the value, so it can be concluded that H1 is accepted and H0 is rejected, which means there is a simultaneous influence and the R square Regression test above shows the value of R Square is 0.155. 3) From the regression equation above, it can be concluded that environmental changes have an influence on the dependent variable (Employee Performance). If there is a Change in the Work Environment, the Employee Performance of Bank Syariah Indonesia Medan Branch will also increase.